Higher Education: Features, Trends and Needs in Sustainability - Maragakis, Antonios; van den Dobbelsteen, Andy (A+BE | Architecture and the Built Environment, 2018)
The progress of sustainability within higher education has steadily increased in focus over the last decade and has increasingly become a topic of academic research. With various scholars, journals and conferences exclusively dealing with the subject, a wealth of literature has been produced on best practices, suggestions, and assessments pertaining to sustainability within the higher education field. Higher education stakeholders, who for this paper are defined as being the potential/ current students, staff and management, continue to become more conscious of the principles of sustainability. This higher level of understanding promotes the needs to assess existing literature in relation to the actual needs of the stakeholders in order to identify existing features, trends and needs so that there is continual improvement in the field. This paper shows that sustainability is currently a socially desirable trait but other factors, such as becoming more competitive in the job market, supersede it in importance to stakeholders. It also shows that there is a general need for a standardized method for assessing institutions, with AASHE’s STARS system being the most used system.